Microencapsulation of cephalexin using ethylcellulose and acrylate-methacrylate copolymer as wall materials - Nathaya Suwanpatra (Chulalongkorn University, 2013)
THesis (M.Sc. in Pharm)--Chulalongkorn University, 1995